Maintaining the Reliability of Aboriginal Oral Records and Their Material Manifestations: Implications for Archival Practice - McRanor, Shauna (Archivaria, 1997)
It can be argued that the need for truthful memory is universal among human populations. But precisely what constitutes truth and how it is preserved varies across cultures and over time, and disparate perspectives and traditions do not always coexist harmoniously. Based on the notion that the apotheosis of material-based memory by Western laws and values has often led to a depreciation of aboriginal oral traditions, this article contends that understanding the process of oral tradition in its endemic juridical context is essential for archivists who handle the material manifestations of this activity. The argument begins by describing, on a very basic level, an example of an aboriginal method of orally creating, transmitting, and preserving records. This exercise helps to demonstrate that materiality is not the only difference between oral and written records; that is, even if oral accounts become affixed to various media, it cannot be assumed that Western requirements for reliability and authenticity are appropriate to assess their veracity. Consequently, the second part of the article proposes that, to maintain the essential qualities of materially manifested oral evidence of action, meaningful consultation between non-native archival institutions and individual First Nations should be undertaken, even if it results in the repatriation of certain items. Respect for the laws and values of aboriginal communities is critical to ensuring that their records are preserved in culturally appropriate ways. RÉSUMÉ Disons, pour fins de discussion, que le besoin d’une mémoire véridique est universel parmi les populations humaines. Toutefois, ce que représente la vérité et comment elle est préservée varie d’une époque à l’autre au sein des différentes cultures; qui plus est, perspectives et traditions différentes ne coexistent pas toujours de manière harmonieuse. Basé sur l’idée que l’apothéose de la mémoire consignée dans les lois et valeurs occidentales a souvent entraîné la dépréciation des traditions orales autochtones, cet article soutient que la compréhension des processus de la tradition orale dans son contexte juridique endémique est essentiel pour les archivistes chargés des manifestations matérielles de cette activité. L’argumentation commence par la présentation d’un exemple, de façon très sommaire, d’une méthode orale employée par les autochtones pour créer, transmettre et préserver des archives. Cet exercice permet de démontrer que la matérialité n’est pas la seule différence entre archives orales ou textuelles. De plus, même si des témoignages oraux sont fixés sur différents supports, on ne peut assumer d’emblée que les exigences occidentales en matière de fiabilité et d’authenticité sont appropriées pour en évaluer la véracité. En conséquence, la deuxième partie de l’article propose qu’il y ait des échanges significatifs entre les dépôts d’archives non-autochtones et chacune des Premières Nations dans le but de préserver les qualités essentielles des formes matérielles des témoignages oraux rendant compte de l’action même si cela doit passer par le rapatriement de certaines pièces. Le respect des lois et valeurs des communautés autochtones est essentiel pour s’assurer que leurs archives soient préservées de façons appropriées sur le plan culturel.